Immune Response to Enterococcus gallinarum in Lupus Patients Is Associated With a Subset of Lupus-Associated Autoantibodies - Bagavant, Harini; Araszkiewicz, Antonina M.; Ingram, Jessica K.; Cizio, Katarzyna; Merrill, Joan T.; Arriens, Cristina; Guthridge, Joel M.; James, Judith A.; Deshmukh, Umesh S. (Frontiers in Immunology, 2021)
Interactions between gut microbes and the immune system influence autoimmune disorders like systemic lupus erythematosus (SLE). Recently, Enterococcus gallinarum, a gram-positive commensal gut bacterium, was implicated as a candidate pathobiont in SLE. The present study was undertaken to evaluate the influence of E. gallinarum exposure on clinical parameters of SLE. Since circulating IgG antibodies to whole bacteria have been established as a surrogate marker for bacterial exposure, anti-E. gallinarum IgG antibodies were measured in banked serum samples from SLE patients and healthy controls in the Oklahoma Cohort for Rheumatic Diseases. The associations between anti-E. gallinarum antibody titers and clinical indicators of lupus were studied. Antibodies to human RNA were studied in a subset of patients. Our results show that sera from both patients and healthy controls had IgG and IgA antibodies reactive with E. gallinarum. The antibody titers between the two groups were not different. However, SLE patients with Ribosomal P autoantibodies had higher anti-E. gallinarum IgG titers compared to healthy controls. In addition to anti-Ribosomal P, higher anti-E. gallinarum titers were also significantly associated with the presence of anti-dsDNA and anti-Sm autoantibodies. In the subset of patients with anti-Ribosomal P and anti-dsDNA, the anti-E. gallinarum titers correlated significantly with antibodies to human RNA. Our data show that both healthy individuals and SLE patients were sero-reactive to E. gallinarum. In SLE patients, the immune response to E. gallinarum was associated with antibody response to a specific subset of lupus autoantigens. These findings provide additional evidence that E. gallinarum may be a pathobiont for SLE in susceptible individuals.